1983
DOI: 10.2527/jas1983.5661393x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Buffers on Ruminal Rate of Passage and Degradation of Soybean Meal in Steers

Abstract: Eight rumen-fistulated steers were randomly assigned to medium- and high-concentrate diets supplemented with 0, .75, 2.5 and 5% of either sodium bicarbonate or an artificial saliva salts mixture. Each animal was fed for 21 d at 75 g dry matter/kg body weight . 75. Rates of soybean meal (SBM) degradation were predicted by adjusting digestion rates in nylon bags with respective passage rates of chromium-mordanted SBM particles. Measures of rumen fermentation were made during the incubation period. Liquid dilutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

1983
1983
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 14 publications
1
19
0
3
Order By: Relevance
“…For instance, the addition of up to 5% bicarbonate in high-concentrate rations improved dry matter intake (DMI) in growing cattle (Nicholson et al, 1963;Wise et al, 1965;Zinn, 1991) but 5% bicarbonate depressed DMI in dairy cows (Emery et al, 1964). Ruminal pH has also been ameliorated in some studies (Nicholson et al, 1963;Okeke et al, 1983;Zinn, 1991), but no effects have been reported in many others (e.g. Thomas and Hall, 1984;Leventini et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the addition of up to 5% bicarbonate in high-concentrate rations improved dry matter intake (DMI) in growing cattle (Nicholson et al, 1963;Wise et al, 1965;Zinn, 1991) but 5% bicarbonate depressed DMI in dairy cows (Emery et al, 1964). Ruminal pH has also been ameliorated in some studies (Nicholson et al, 1963;Okeke et al, 1983;Zinn, 1991), but no effects have been reported in many others (e.g. Thomas and Hall, 1984;Leventini et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: Alfred.Ferret@uab.es fermentation and passage rates, water consumption and blood biochemistry (Erdman, 1988). Therefore, different approaches to avoid confounding factors have been used: fixing the forage-to-concentrate ratio (Okeke et al, 1983;Hart and Polan, 1984); restricting the daily roughage intake (Emery et al, 1964) or the total ration daily intake (Nicholson et al, 1963;Okeke et al, 1983;Quigley et al, 1992); withholding feed on the day before sampling (Thomas and Hall, 1984); intra-ruminal infusions of BICARB (Rogers and Davis, 1982b); or even training the calves during the adaptation period to eat meals by removing feed shortly after feeding to facilitate pulse dosing of BICARB (Hart and Polan, 1984). However, there is little information on the effects of buffer addition on intake and ruminal fermentation when animals have ad libitum access to concentrate and roughage in intensive beef production systems.…”
Section: Introductionmentioning
confidence: 99%
“…Further-more. the effect of bicarbonate on rumen ammonia levels is still a controversial issue (Okeke et al 1983;Haaland and Tyrrell 1982). The absence of the usual increase in rumen ammonia shortly after I'eeding the HP diet (Fig.…”
mentioning
confidence: 99%
“…The increase in water intake with the addition of NaCl to the diet was expected as this effect has been shown previously both in cattle (Rogers, Marks, Davis and Clark, 1979;Rogers and Davis, 1980), and in sheep (Peirce, 1957). Similarly, the infusion or addition of buffer salts was shown to increase the liquid outflow from the rumen of steers (Rogers et al, 1979;Rogers and Davis, 1980;Okeke, Buchanan-Smith and Grovum, 1983 and from the rumen of sheep Osbourn, 1975 and1976). In the present experiment addition of NaCl had no significant effect on FRO of Crtreated fish meal from the rumen in contrast to the significant (P < 0-05) linear increase in FRO of Cr-mordanted soya bean meal from the rumen of steers given buffer salts (Okeke et al, 1983).…”
Section: Discussionmentioning
confidence: 55%